2021
DOI: 10.3389/fpubh.2021.588254
|View full text |Cite
|
Sign up to set email alerts
|

Food Insecurity: A Constant Factor in the Lives of Low-Income Families in Scotland and England

Abstract: During the school summer holidays, pressures on the already tight budgets of low-income families are compounded, particularly when the safety net of free school meals is removed. The main aim of the current study was to investigate how low-income parents and carers feed their families during term time when children receive free school meals and if, and how, strategies differ during the school summer holidays. A secondary aim was to investigate the role of holiday activity and food programmes in supporting pare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…During term-time, almost 20% of school-aged children in England are eligible for free school meals [ 1 , 2 ], with research by The Food Foundation demonstrating that approximately 2.5 million children experienced food insecurity in the six months up until July 2021. Problematically, however, without free school meal provision during school holiday periods, many families face increased financial pressures and are at further risk of food insecurity, known as holiday hunger [ 3 , 4 ]. To alleviate these issues, holiday clubs, which extend beyond solely providing access to food, have formed over recent years [ 5 , 6 ] and research has demonstrated significant social and health benefits of attendance, both for school-aged children and their wider families [ 7 , 8 , 9 ]; with food insecure households benefitting most from holiday provision [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…During term-time, almost 20% of school-aged children in England are eligible for free school meals [ 1 , 2 ], with research by The Food Foundation demonstrating that approximately 2.5 million children experienced food insecurity in the six months up until July 2021. Problematically, however, without free school meal provision during school holiday periods, many families face increased financial pressures and are at further risk of food insecurity, known as holiday hunger [ 3 , 4 ]. To alleviate these issues, holiday clubs, which extend beyond solely providing access to food, have formed over recent years [ 5 , 6 ] and research has demonstrated significant social and health benefits of attendance, both for school-aged children and their wider families [ 7 , 8 , 9 ]; with food insecure households benefitting most from holiday provision [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…However there is only a significant relationship between knowledge and undernutrition. This result could be because even though the attitude of the mother on eating behavior was good, the low-income families may have limitations to meet their daily needs so that the attitude of the mother on eating behavior was not significantly related (Seo & Park, 2021;Shinwell & Defeyter, 2021).…”
Section: Discussionmentioning
confidence: 97%
“…The conceptual basis developed during this research and used to underpin the comprehensive household food security tool highlights the complex nature of food security. Risk factors for food insecurity are commonly attributed to economic variables such as low income and unemployment [ 26 , 27 , 28 ]. Health risk factors such as maternal depression have also consistently been found to be higher among women experiencing food insecurity [ 29 ].…”
Section: Discussionmentioning
confidence: 99%